Jurastuderende bag tremmer: – Transformativ læring og social forandring - Kjær Minke, Linda (Nordisk Tidsskrift for Kriminalvidenskab, 2023)
Abstract Since 2016, Søbysøgård Prison and the Department of Law at the University of Southern Denmark (SDU) have partnered to offer the course »Crime, Punishment, and Crime Preventive Strategies.« The course is inspired by the Inside-Out Prison Exchange Program, which was established in the USA in 1997 and has spread to several countries since then. The teaching is conducted at Søbysøgård Prison’s closed wing with the participation of 12 law students from SDU (outside students) and 12 incarcerated men at Søbysøgård Prison (inside students). In 2022, a total of 150 students had completed the course. The article describes students’ experiences with the course based on an analysis of student motivation applications, evaluations of the course, and teacher reflections. The research finds that the course extends students’ knowledge of criminal justice matters. In addition, the program appears to support critical thinking among students and transform problematic frames of references, which results in transformative learning. The article also reflects on the programme’s potential risks and benefits.